tBRD-1 and tBRD-2 regulate expression of genes necessary for spermatid differentiation. - Theofel, I.; Bartkuhn, M.; Boettger, T.; Gärtner, S.M.K.; Kreher, J.; Brehm, A.; Rathke, C. (Biology open, 2017)
Male germ cell differentiation proceeds to a large extent in the absence of active gene transcription. In Drosophila, hundreds of genes whose proteins are required during post-meiotic spermatid differentiation (spermiogenesis) are transcribed in primary spermatocytes. Transcription of these genes depends on the sequential action of the testis meiotic arrest complex (tMAC), Mediator complex, and testis-specific TFIID (tTFIID) complex. How the action of these protein complexes is coordinated and which other factors are involved in the regulation of transcription in spermatocytes is not well understood. Here, we show that the bromodomain proteins tBRD-1 and tBRD-2 regulate gene expression in primary spermatocytes and share a subset of target genes. The function of tBRD-1 was essential for the sub-cellular localization of endogenous tBRD-2 but dispensable for its protein stability. Our comparison of different microarray data sets showed that in primary spermatocytes, the expression of a defined number of genes depends on the function of the bromodomain proteins tBRD-1 and tBRD-2, the tMAC component Aly, the Mediator component Med22, and the tTAF Sa.